Case report: A case of tetanus in a dog: cranial nerve involvement and imaging findings - Grant, Kylie; Long, Sam (Frontiers in Veterinary Science, 2023)
An 11-year old male Labrador cross presented with unilateral vestibular signs, ipsilateral facial paresis, moderate obtundation, ptyalism and paraparesis. MRI of the brain revealed diffuse, multifocal T2/FLAIR hyperintense changes throughout various regions of the brain including the medulla, midbrain, pons, thalamus and right cerebral hemisphere with mild multifocal contrast enhancement. The patient progressed to trismus with generalized increased extensor tone and risus sardonicus. A diagnosis of generalized tetanus was made and the patient was started on antibiotics, skeletal muscle relaxants and tetanus antitoxin and made a full recovery. To the best of the authors' knowledge, this is the first reported case of canine tetanus in which the presenting signs involved cranial nerve dysfunction as well as the first report describing MRI changes in canine tetanus within the central nervous system.